Pengembangan Media Scrapbook pada Pembelajaran IPS Siswa Kelas V di SD Negeri 95 Palembang - Nyimas Edwiliyah Ryatanti; Ilham Arvan Junaidi; Imelda Ratih Ayu (Departement of Mathematics Education, 2024)
This study was conducted to determine the validity and practicality of scrapbook learning media developed in social studies learning material on the type of business of Indonesian society. The type of research is Research and Development. The model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The product validity test was carried out by filling out a questionnaire given to three experts, namely media experts, material experts, and language experts, and the product practicability test was carried out to teachers and students of class V B. The data obtained were obtained from observations, interviews, questionnaires, and documentation. The data analysis technique used was data analysis of product validity and practicality. The results of the acquisition of validity data values obtained from experts get an average score of 78.8% with a valid category based on questionnaire criteria data. The practicality of scrapbook media was assessed by distributing student and teacher response questionnaires. At the small group stage, the score was 85.8%, at the large group stage, the score was 80.7%, and the teacher response questionnaire obtained a score of 91.1% with an average overall score obtained of 85.8% with a very practical category based on questionnaire criteria. Thus, it can be concluded that the scrapbook media is included in the valid category and is very practical to use.